5/2t - t = 3 + 3/2t

We will combine like terms,

==> 5/2t - 3/2t - t= 3

==> (5-3)/2t - t = 3

==> 2/2t - t = 3

==> 1/t - t= 3

==> Multiply by t.

==> 1 - t^2 = 3t

==> t^2 + 3t -1 = 0

==> t= [ -3 + sqrt(9+4)/ 2 = (-3+sqrt13)/ 2

==> t2= (-3-sqrt13)/2

Then we have two solution.

**==> t= { (-3+sqrt13)/2 , (-3-sqrt13)/2 }**

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now